Q: What does 3b mean in .7500-16 unfj-3b?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

If you mean: (3b+7)^2 then it is 9b^2+42b+49

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b

a = 3b - c a + c = 3b - c + c a + c = 3b (a + c)/3 = 3b/3 ( a + c ) / 3 = b Do your homework.

To simplify the expression 3b^2 - 3b, we first factor out the common factor of 3b. This gives us 3b(b - 1), where b - 1 is the simplified form of the expression. This expression represents the difference between 3 times the square of a variable b and 3 times the variable b.

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

Related questions

If you mean 3b+9 = 12 then b equals 1

Third Base

If you mean: (3b+7)^2 then it is 9b^2+42b+49

6b^2 - 3b / 3b 6b^2 - 1 or ( 6b^2 - 3b) / 3b = 2b - 1 Or (6b^2 - 3b ) / 3b = 3b(2b - ) / 3b = 2b - 1

Firstly, I think you mean 2a-3b. The numbers always come first. Secondly, 2a-3b is an expression, not an equation as equations have equeal signs in them. Lastly, you do not have enough information to solve 2a-3b since it is an expression. Therefore, the answer to your question is 2a-3b.

If you mean: 6(-3b-1)+2(7b-1) then it is -4b-8 simplified

Since 3b is a factor of 9b, it is automatically the GCF.

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b

a = 3b - c a + c = 3b - c + c a + c = 3b (a + c)/3 = 3b/3 ( a + c ) / 3 = b Do your homework.

If 3b = 39 thenb = 39/3b = 13.

3b

3b-8b = -5